Private equity: where we have been and the road ahead. Issue 1 (2nd January 2019) - Wright, Mike; Pruthi, Sarika; Amess, Kevin; Alperovych, Yan
ABSTRACT: We provide an overview of the systematic evidence relating to the impact of private equity (PE) backed buyouts over the last two decades. We focus on performance; employment and employee relations; innovation, investment and entrepreneurship; longevity and survival. We also explore a future research agenda in the context of a maturing PE industry.